The efficacy and safety of endoscopic double J stent versus open ureteric re-implantation of primary obstructive megaureter in pre-school children 1-5 years - Jabbar, Abdul; Ullah, Hazrat; Ahmad, Tariq; Iqbal, Mohammad Anees; Sabir, Muhammad (International Journal of Pathology, 2025)
Background: Primary obstructive megaureter (POM) is not uncommon in our population, and urologists treat it differently depending on their experience and personal preferences. In addition, there is conflicting information in the literature about the endoscopic placement of a double J stent in POM patients. This study will give us a local magnitude comparison of endoscopic implantation of JJ stents with open surgery in treating POM. Methods: The Department of Urology at the Khyber Teaching Hospital Peshawar ran this comparative analytical study from July 2024 to July 2025. The study included 102 patients, 51 in each group, who were between the ages of 1 and 5 years and had primary obstructive mega ureter. We did not include patients with bladder stone, neurogenic bladder and who have received any treatment for POM in the past. While patients in group B underwent open ureteric re-implantation, patients in group A underwent endoscopic double J stent insertion. If the obstruction is removed and the ureteral diameter and hydronephrosis decrease, the procedure was deemed successful. If there were no complications during the eighth week of follow-up, the surgery was deemed safe. Results: In my investigation, the efficacy of endoscopic double J stents and open ureteric surgery re-implantation was 64.71% and 92.16%, respectively, with a p-value of 0.0008. The safety of endoscopic double J stents and open ureteric surgery re-implantation was 80.39% and 96.08%, respectively, with a p-value of 0.014. Conclusion: We came to the conclusion that open ureteric surgery is more effective and safer than endoscopic double J stents for re-implantation of primary obstructive megaureters in preschoolers aged 1 to 5.